Effects of Shirasu natural pozzolan and limestone powder on the strength and aggressive chemical resistance of concrete. (10th April 2020) - Pham, Van Toan; Meng, Phalkong; Bui, Phuong Trinh; Ogawa, Yuko; Kawai, Kenji
Highlights: Concrete deterioration in a mixed solution containing H2 SO4 and MgCl2 was studied. Using Shirasu as a fine aggregate replacement improved concrete strength. Incorporating Shirasu improved concrete resistance to aggressive chemicals. Effect of using limestone powder on concrete strength development was insignificant. Concretes containing limestone powder suffered more severe chemical deterioration. Abstract: This study investigated the effects of using limestone powder and Shirasu natural pozzolan, as partial replacements for fine aggregate, on the mechanical properties and resistance of concrete to an aggressive solution containing 3% H2 SO4 and 5% MgCl2 . The data show that replacing 5% of the fine aggregate with limestone powder results in more severe deterioration of the concrete by the chemical solution. However, replacing 55% of the fine aggregate with Shirasu both increases compressive strength after a 28-day cure and improves chemical resistance of concrete. In addition, the deterioration mechanism of concrete immersed in the aggressive solution was examined in this study.